Does Decentralisation Lead to Improvement in Planning of Health Services? Findings from Six District Health Administrations in Ghana - Sakyi, E. K.; Azunu, R.; Bawole, J. N. (My University, 2011)
This study examines the extent to which decentralization is transforming health sector planning in Ghana with a focus on the experiences of six District Health Administrations. It examines the impact and implications of decentralization for planning and implementation of health programmes in the public health sector at the district level and identifies specific changes in the structures, actors, processes and procedures resulting from decentralization. Fieldwork for the study was conducted in six District Health Administrations in five regions, namely, Upper East, Northern, Brong Ahafo, Ashanti and Eastern regions. The study concludes that, despite the many obstacles, decentralization is impacting positively upon health planning structures, actors and processes; and, it is actually a better alternative to a centralized planning system.
Keywords: public health; decentralization; health policy